A biocompatible hybrid material with simultaneous calcium and strontium release capability for bone tissue repair - Almeida, J. Carlos; András Wacha; Gomes, Pedro S.; Alves, Luís C.; Fernandes, M. Helena Vaz; Salvado, Isabel M. Miranda; Fernandes, M. Helena R. (Materials Science and Engineering: C, 2016)
The increasing interest in the effect of strontium in bone tissue repair has promoted the development of bioactive materials with strontium release capability. According to literature, hybrid materials based on the system PDMS–{}SiO2 have been considered a plausible alternative as they present a mechanical behavior similar to the one of the human bone. The main purpose of this study was to obtain a biocompatible hybrid material with simultaneous calcium and strontium release capability. A hybrid material, in the system PDMS–{}SiO2–{}CaO–{}SrO, was prepared with the incorporation of 0.05 mol of titanium per mol of SiO2. Calcium and strontium were added using the respective acetates as sources, following a sol–{}gel technique previously developed by the present authors. The obtained samples were characterized by FT-IR, solid-state NMR, and SAXS, and surface roughness was analyzed by 3D optical profilometry. In vitro studies were performed by immersion of the samples in Kokubo's SBF for different periods of time, in order to determine the bioactive potential of these hybrids. Surfaces of the immersed samples were observed by SEM, EDS and PIXE, showing the formation of calcium phosphate precipitates. Supernatants were analyzed by ICP, revealing the capability of the material to simultaneously fix phosphorus ions and to release calcium and strontium, in a concentration range within the values reported as suitable for the induction of the bone tissue repair. The material demonstrated to be cytocompatible when tested with MG63 osteoblastic cells, exhibiting an inductive effect on cell proliferation and alkaline phosphatase activity.
Keywords: Biocompatible; Hybrid materials; peer-reviewed; Strontium

Nanostructure Research by Small-Angle X-Ray Scattering: From Instrument Design to New Insights in Materials Sciences - András Wacha (Physics, 2016)
My thesis work presents the versatility of the small-angle X-ray scattering (SAXS) method in the structural research of nanomaterials. It contains the details of the design and construction of a new, highly effective laboratory SAXS instrument. The uniqueness of this apparatus—{}even by international standards—{}lies in the extremely broad small- and wide-angle range, and its high signal-to-noise ratio. This is ensured by the special optimization method developed for the beam shaping system. The performance of the instrument is further enhanced by the custom-made instrument control software and data analysis framework, the flexibility and accuracy of which is outstanding even among synchrotron SAXS beamlines. Due to these special methods, material systems which are too weak scatterers for traditional laboratory cameras became measurable on this apparatus. I have validated the instrument by accurately determining the size distribution of spherical SiO2 nanoparticles. Other new scientific results obtained using this instrument are presented on case studies of size and shape determination of protein solutions, and in situ characterization of a self-assembling gold-cysteine photoluminescent nanocomplex. Additionally, results on the anisotropy in wood-derived activated carbons are also presented, showcasing the possibilities of SAXS on complex hierarchical systems, as well as the algorithms developed for the instrument and SAXS data interpretation in general.

Amfifil polimer kotérhálók: egy újszerű nanoszerkezetű anyagcsoport - Szabó, Ákos; Mezey, Péter; Fodor, Csaba; Domján, Attila; Kali, Gergely; Stumphauser, Tímea; Erdődi, Gábor; Thomann, Ralf; Németh, Péter; Szanka, István; Illés, Gergely; Haraszti, Márton; et al. (Magyar Kémiai Folyóirat - Kémiai Közlemények, 2015)
Keywords: no-peer-review

Effects of ursolic acid on the structural and morphological behaviours of dipalmitoyl lecithin vesicles - Lőrincz, András; Mihály, Judith; Németh, Csaba; András Wacha; Bóta, Attila (Biochimica et Biophysica Acta (BBA) - Biomembranes, 2015)
Effects of ursolic acid on the structural and morphological characteristics of dipalmitoyl lecithin(DPPC)-water system was studied by using differential scanning calorimetry (DSC), small- and wide-angle X-ray scattering (SWAXS), freeze-fracture method combined with transmission electron-microscopy (FF-TEM) and infrared spectroscopy (FT-IR). The surface of the uncorrelated lipid system is rippled or grained and a huge number of small, presumably unilamellar vesicles are present if the UA/DPPC molar ratio is 0.1 mol/mol or higher. Besides the destroyed layer packing of regular multilamellar vesicles, non-bilayer (e.g. cubic or hexagonal) local structures are evidenced by SAXS and FF-TEM methods. The ability of UA to induce non-bilayer structures in hydrated DPPC system originates from the actual geometry form of associated lipid and UA molecules as concluded from the FT-IR measurements and theoretical calculations. Beside numerous beneficial e.g. chemopreventive and chemotherapeutic effect of ursolic acid against cancer, their impact to modify the lipid bilayers can be utilized in liposomal formulations.
Keywords: DPPC; Freeze-fractured transmission electron-microscopy (FF-TEM); Kratky camera; Non-bilayer lipid structure; peer-reviewed; Small- and wide-angle X-ray scattering (SWAXS); Ursolic acid

Inherently fluorescent and porous zirconia colloids: preparation, characterization and drug adsorption studies - Naszályi Nagy, Lívia; Mihály, Judith; Polyák, András; Debreczeni, Balázs; Császár, Barbara; Szigyártó, Imola Csilla; András Wacha; Czégény, Zsuzsanna; Jakab, Emma; Klébert, Szilvia; Drotár, Eszter; Dabasi, G; et al. (J. Mater. Chem. B, 2015)
Porous, fluorescent zirconia particles of nearly 380 nm diameter were prepared without template molecules or labeling dyes. The porous structure is the result of aggregation-induced particle formation. The inherent fluorescence is assigned to coordinatively unsaturated Zr4+ ions at the sol–{}gel derived ZrO2 surface. After physico-chemical characterization of the native zirconia particles carboxyl and/or amine bearing drug molecules (D,L-\ensuremath{α}-difluoromethylornithine –{} DFMO, ursolic acid –{} UA and doxorubicin –{} DOX) were adsorbed onto their surface, and the products were analyzed with Fourier-transform infrared spectroscopy (FTIR), thermogravimetry (TG), small-angle X-ray scattering (SAXS), fluorimetry and zeta potential vs. pH measurements. We have found that DOX complexes coordinatively unsaturated Zr4+ ions without dislocating them, while carboxyl-bearing drugs interact with basic surface Zr–{}OH sites eliminating some of the carbonate species. The adsorption of UA at the zirconia surface shifts considerably the isoelectric point of the surface and thus provides kinetic stability to the particles at physiological pH. An in vivo biodistribution study in two healthy dogs performed by SPECT/CT detection after 99mTc labeling of the nanocarriers has shown the possibility of drug delivery application.
Keywords: peer-reviewed

Nanoszerkezetek meghatározásának új hazai lehetőségei a CREDO kisszögű röntgenszórásos nagyberendezéssel - Bóta, Attila; Varga, Zoltán; András Wacha (Magyar Kémikusok Lapja, 2015)
Keywords: CREDO

Optimized Pinhole Geometry for Small-Angle Scattering - András Wacha (Journal of Applied Crystallography, 2015)
In order to make the most from the low photon flux in laboratory small-angle X-ray scattering instruments, the experimental geometry has to be chosen carefully, with special stress on the beam-shaping system. The optimum collimation scheme should enable accurate measurements over the desired range of the scattering variable, while yielding the highest flux and the lowest possible instrumental background. In order to identify the best setting, a phase-space optimization of the collimating scheme is carried out in the present work, including constraints on the beam size at the sample position and on the detector surface. The resulting formulae are implemented in a Python script with a graphical user interface, to aid the planning, construction and daily operation of pinhole small-angle scattering cameras.
Keywords: CREDO

PDMS-SiO2 hybrid materials – A new insight into the role of Ti and Zr as additives - Almeida, J. Carlos; András Wacha; Bóta, A.; Almásy, L.; Vaz Fernandes, M. Helena; Margaça, Fernanda M. A.; Miranda Salvado, Isabel M. (Polymer, 2015)
The last two decades have seen a remarkable growth in the design of new hybrid materials applied to different areas, from photonics to biomaterials, together with new coating materials with self-cleaning features. Among the various systems studied, the PDMS-SiO2 system remains as a good basis for further developments by adding other compounds such as transition metals. In this work, a detailed study of the influence of titanium or zirconium in the chemical structure and final microstructure of such hybrids was made. It was concluded that, due to the lower reactivity of the titanium alkoxide during the sol–gel preparation process, titanium is preferably located on the surface of secondary particles of silica, unlike the zirconium, which being more reactive, positions on the surface of the primary particles. This difference leads to xerogels with dissimilar characteristics and morphologies.
Keywords: CREDO; Hybrid materials; Sol–gel; Structure

Physicochemical characterization of artificial nanoerythrosomes derived from erythrocyte ghost membranes - Deák, Róbert; Mihály, Judith; Szigyártó, Imola Cs.; András Wacha; Lelkes, Gábor; Bóta, Attila (Colloids and Surfaces B: Biointerfaces, 2015)
Colloidal stabile nanoerythrosomes with 200 nm average diameter were formed from hemoglobin-free erythrocyte ghost membrane via sonication and membrane extrusion. The incorporation of extra lipid (1,2-dipalmitoyl-sn-glycero-3-phosphocholine, DPPC), added to the sonicated ghosts, caused significant changes in the thermotropic character of the original membranes. As a result of the increased DPPC ratio the chain melting of the hydrated DPPC system and the characteristic small angle X-ray scattering (SAXS) of the lipid bilayers appeared. Significant morphological changes were followed by transmission electron microscopy combined with freeze fracture method (FF-TEM). After the ultrasonic treatment the large entities of erythrocyte ghosts transformed into nearly spherical nanoerythrosomes with diameters between 100 and 300 nm and at the same time a great number of 10–30 nm large membrane proteins or protein clusters were dispersed in the aqueous medium. The infrared spectroscopy (FT-IR) pointed out, that the sonication did not cause changes in the secondary structures of the membrane proteins under our preparation conditions. About fivefold of extra lipid – compared to the lipid content of the original membrane – caused homogeneous dispersion of nanoerythrosomes however the shape of the vesicles was not uniform. After the addition of about tenfold of DPPC, monoform and monodisperse nanoerythrosomes became typical. The outer surfaces of these roughly spherical objects were frequently polygonal, consisting of a net of pentagons and hexagons.
Keywords: CREDO; Erythrocyte; Freeze fracture TEM; Infrared spectroscopy; Nanoerythrosomes; Protein to lipid ratio; Small angle X-ray scattering (SAXS); Vesicles

The supramolecular chemistry of gold and l-cysteine: Formation of photoluminescent, orange-emitting assemblies with multilayer structure - Söptei, Balázs; Mihály, Judith; Szigyártó, Imola Cs.; András Wacha; Németh, Csaba; Bertóti, Imre; May, Zoltán; Baranyai, Péter; Sajó, István E.; Bóta, Attila (Colloids and Surfaces A: Physicochemical and Engineering Aspects, 2015)
Keywords: CREDO

Synthesis of Poly}(methyl methacrylate)-poly(poly(ethylene glycol) methacrylate)-polyisobutylene ABCBA Pentablock Copolymers} by Combining Quasiliving Carbocationic} and Atom Transfer Radical Polymerizations} and Characterization Thereof} - Szabó, Ákos; András Wacha; Thomann, Ralf; Szarka, Györgyi; Bóta, Attila; Iván, Béla (Journal of Macromolecular Science, Part A, 2015)
Keywords: Kratky camera; peer-reviewed

Szervetlen gyógyszerhordozó nanorészecskék el\H oáll{ítása és jellemzése - Nagyné Naszályi, Lívia; Pálmai, Marcell; Peth\H o, Adrienn; Császár, Barbara; Polyák, András; Szigyártó, Imola Csilla; Mihály, Judith; András Wacha; L\H orincz, András (Magyar Kémiai Folyóirat - Kémiai Közlemények, 2015)
Keywords: no-peer-review

Vanadium dispersion and catalytic activity of Pd/VOx/SBA-15 catalysts in the Wacker oxidation of ethylene - Barthos, Róbert; Hegyessy, András; Klébert, Szilvia; Valyon, József (Microporous and Mesoporous Materials, 2015)
Transmission electron microscopy (TEM), X-ray diffractometry (XRD), in situ diffuse reflectance ultra violet – visible (UV–Vis) spectroscopy, and temperature-programmed reduction by hydrogen (H2-TPR) were used to identify the vanadia forms in vanadium-containing SBA-15 preparations (VOx/SBA-15). Wacker type supported Pd/VOx/SBA-15 catalysts were obtained by introducing Pd into VOx/SBA-15 samples using conventional impregnation method. The activity of the catalysts was tested in the gas phase partial oxidation of ethylene by O2 in the presence of H2O (Wacker oxidation). VOx/SBA-15 sample was obtained by micelle-templated synthesis using vanadium-containing synthesis gel. The vanadium became incorporated in the silica structure from the gel in near to atomic dispersion. This catalyst was quite active in ethylene oxidation to CO2 but had low Wacker activity. Isolated, polymeric and bulk vanadia species were identified in the VOx/SBA-15 prepared by wet impregnation/calcination method. The specific surface area of the sample was found to be smaller than that of the neat SBA-15 support because some pores were blocked by vanadia agglomerates. The corresponding Pd/VOx/SBA-15 catalyst showed high selectivity for acetaldehyde formation but the activity was relatively low due to low accessible active surface. A third VOx/SBA-15 sample was obtained by applying directed surface reaction between silanol groups of dehydrated SBA-15 and anhydrous solution of vanadyl acetylacetonate. Large number of accessible Pd/VOx sites were present in the corresponding Pd/VOx/SBA-15 catalyst. Latter catalyst induced ethylene oxidation to acetaldehyde with high yield at temperatures ≤160 °C and with good yield to acetic acid at temperatures ≥160 °C.
Keywords: H2-TPR; Pd/V catalysts; SBA-15; UV–Vis; Wacker oxidation

CREDO: a new general-purpose laboratory instrument for small-angle X-ray scattering - András Wacha; Varga, Zoltán; Bóta, Attila (Journal of Applied CrystallographyJournal of Applied Crystallography, 2014)

Effect of metal oxide on surface area and pore size of water-dispersible colloids from three German silt loam topsoils - Jiang, Canlan; Séquaris, Jean-Marie; András Wacha; Bóta, Attila; Vereecken, Harry; Klumpp, Erwin (Geoderma, 2014)
Keywords: CREDO

Intercalation of Bovine Serum Albumin Coated Gold Clusters Between Phospholipid Bilayers: Temperature-Dependent Behavior of Lipid-AuQC@BSA Assemblies with Red Emission and Superlattice Structure - Söptei, Balázs; Mihály, Judith; Visy, Júlia; András Wacha; Bóta, Attila (The Journal of Physical Chemistry B, 2014)
A method has been developed to encapsulate bovine serum albumin (BSA)-coated gold quantum clusters (AuQC@BSA) in a multilamellar system of dipalmitoylphosphatidylcholine (DPPC). Results have shown that intercalation of AuQC@BSA particles into lipid bilayers occurs in the presence of CaCl2. Intense red photoluminescence emission was observed after encapsulation of the clusters. A well-defined structure was found with periodic distances drastically larger than that in the pure DPPC/water system. Although Ca2+ ions can change the dipole characteristics of the lipid bilayer surface, leading to unbinding between the bilayers of multilamellar DPPC/water system, the repulsion is shielded in the presence of AuQC@BSA particles. A coherent superlattice structure evolves due to mixed Ca2+-DPPC and Ca2+-AuQC@BSA interactions. Studies at different temperatures have suggested a correlation between the luminescence properties of the clusters and phase transition of the lipid layers. The temperature-dependent behavior assumes the connection between the coating and the lipid bilayer surface. Temperature-dependent features of lipid intercalated Au clusters provide new opportunities in their application.

Osmotic shrinkage of sterically stabilized liposomes as revealed by time-resolved small-angle X-ray scattering - Varga, Zoltán; András Wacha; Bóta, Attila (Journal of Applied Crystallography, 2014)

Mechanical Stability and Fibrinolytic Resistance of Clots Containing Fibrin, DNA, and Histones - Longstaff, Colin; Varjú, Imre; Sótonyi, Péter; Szabó, László; Krumrey, Michael; Hoell, Armin; Bóta, Attila; Varga, Zoltán; Komorowicz, Erzsébet; Kolev, Krasimir (Journal of Biological ChemistryJournal of Biological Chemistry, 2013)
Neutrophil extracellular traps are networks of DNA and associated proteins produced by nucleosome release from activated neutrophils in response to infection stimuli and have recently been identified as key mediators between innate immunity, inflammation, and hemostasis. The interaction of DNA and histones with a number of hemostatic factors has been shown to promote clotting and is associated with increased thrombosis, but little is known about the effects of DNA and histones on the regulation of fibrin stability and fibrinolysis. Here we demonstrate that the addition of histone-DNA complexes to fibrin results in thicker fibers (increase in median diameter from 84 to 123 nm according to scanning electron microscopy data) accompanied by improved stability and rigidity (the critical shear stress causing loss of fibrin viscosity increases from 150 to 376 Pa whereas the storage modulus of the gel increases from 62 to 82 pascals according to oscillation rheometric data). The effects of DNA and histones alone are subtle and suggest that histones affect clot structure whereas DNA changes the way clots are lysed. The combination of histones + DNA significantly prolongs clot lysis. Isothermal titration and confocal microscopy studies suggest that histones and DNA bind large fibrin degradation products with 191 and 136 nm dissociation constants, respectively, interactions that inhibit clot lysis. Heparin, which is known to interfere with the formation of neutrophil extracellular traps, appears to prolong lysis time at a concentration favoring ternary histone-DNA-heparin complex formation, and DNase effectively promotes clot lysis in combination with tissue plasminogen activator.
Keywords: DNA; Fibrinolysis; Histones; Neutrophil; Neutrophil Extracellular Trap; Tissue Plasminogen Activator (tPA)

Probing Nanoscale Structures - The SANS Toolbox - Hammouda, Boualem (Probing Nanoscale Structures - The SANS ToolboxProbing Nanoscale Structures - The SANS Toolbox, 2012)

Small-angle X-ray scattering experiments and computer simulations to characterise anisotropy of activated carbons prepared from wood - András Wacha; Varga, Zoltán; Vainio, Ulla; Hoell, Armin; Bóta, Attila (CarbonCarbon, 2011)

A Closer Look at the Structure of Sterically Stabilized Liposomes: A Small-Angle X-ray Scattering Study - Varga, Zoltán; Berényi, Szilvia; Szokol, Bálint; Őrfi, László; Kéri, György; Peták, István; Hoell, Armin; Bóta, Attila (The Journal of Physical Chemistry BThe Journal of Physical Chemistry B, 2010)

X-ray Data Booklet - Attwood, David; Gullikson, Eric; Howells, Malcolm; Kim, Kwang-Je; Kirz, Janos; Kortright, Jeffrey; Lindau, Ingolf; Liu, Yanwei; Pianetta, Piero; Robinson, Arthur; Scofield, James; Underwood, James; et al. (Lawrence Berkeley National Laboratory, University of California, 2009)

Electrically tunable color of mixtures of bent-core and rod-shaped molecules - Nair, GG; Bailey, C; Taushanoff, Stefanie; Fodor-Csorba, Katalin; Vajda, Anikó; Varga, Zoltán; Bóta, Attila; Jákli, Antal (Advanced MaterialsAdvanced Materials, 2008)

Structural Description of the Nickel Part of a Raney-Type Catalyst by Using Anomalous Small-Angle X-ray Scattering - Bóta, Attila; Varga, Zoltán; Goerigk, Günter (Journal of Physical Chemistry CJournal of Physical Chemistry C, 2008)

Unbinding Transition in Lipid Multibilayers Induced by Copper(II) Ions - Varga, Zoltán; Bóta, Attila; Goerigk, Günter (The Journal of Physical Chemistry BThe Journal of Physical Chemistry B, 2008)

Az anyagvizsgálat diffrakciós módszerei - Schultz, Jerold M (Műszaki Könyvkiadó, 1987)

Structure Analysis by Small-Angle X-Ray and Neutron Scattering - Feigin, L. A.; Svergun, D. I. (Plenum Press, 1987)

Small angle X-ray scattering - Glatter, Otto; Kratky, Otto (Academic Press, 1982)
Keywords: Science / Physics / Electromagnetism; Science / Radiation; Small-angle scattering; Small-angle x-ray scattering; Small-angle x-ray scattering - Scientific applications; Small-angle x-ray scattering/ Scientific applications; Technology & Engineering / General; X-ray crystallography; X-ray crystallography - Scientific applications; X-ray crystallography/ Scientific applications; X-rays

X-ray diffraction by polymers - Kakudo, Masao; Kasai, Nobutami (Kodansha, 1972)
Keywords: Polymers; Science / Physics / Crystallography; Science / Physics / Optics & Light; Technology & Engineering / Textiles & Polymers; X-ray crystallography; X-rays; X-rays - Diffraction

Small-angle scattering of X-rays - Guinier, André; Fournet, Gérard (John Wiley & Sons, Inc., 1955)